Identification of Two Aphids’ (Aphis craccivora Koch) Biotypes Prevailing in Three Cowpea (Vigna unguiculata (L). Walp.) Growing Areas in Burkina Faso - Ouedraogo, Adélaïde P.; Tignegre, Jean-Baptiste; Traore, Fousseni; Batieno, Benoit J.; Ouedraogo, Theodore Y.; Bama, Herve; Ouedraogo, Jeremy T. (European Journal of Applied Sciences, 2024)
Cowpea (Vigna unguiculata (L). Walp.) is a plant-based protein crop with high nutritional value but highly susceptible to insect pests, particularly aphids (Aphis craccivora Koch). Aphids can destroy 80 to 100% of cowpea farms and also transmit viral diseases like cowpea mosaic virus, significantly reducing yields. This study aimed to investigate the evolution of aphid infestations from three cowpea-growing locations of Burkina Faso (Bobo, Kamboinsé, and Pobé) and identify the prevailing aphid biotypes. Therefore, ten varieties were screened with three aphids’ strains from these locations. A randomized complete block design with three (3) blocks and five (5) repetitions each was used. The number of leaves per plant, the survival of individual plant and the degree of infestation were evaluated. Results revealed that the degree of infestation used as a criterion for evaluating cowpea resistance to aphids is just as reliable during the early stages of plants development as during the following stages. Two biotypes of aphids have been identified. Indeed, the Kamboinse strain is similar to that of Pobé and these two strains are significantly different from the strain of Bobo. The close relationship between the 2 biotypes suggests the possibility to develop varieties strong enough to resist to both of them. A molecular characterization of the three aphids’ strains would provide more precision on the genetics of the two aphides’ biotypes.